2016
DOI: 10.2174/1381612822666160531163144
|View full text |Cite
|
Sign up to set email alerts
|

Polyketide Natural Products, Acetogenins from Graviola (Annona muricata L), its Biochemical, Cytotoxic Activity and Various Analyses Through Computational and Bio-Programming Methods

Abstract: To predict and decipher the activity of various acetogenins in Annona muricata and its potent activity towards the inhibition of cancer cell lines, it is interesting to look out for the potent lead compound against the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A. muricata has also been used, mainly in developing tropical countries, for the treatment of arthritis [ 61 ], hypertension [ 62 ], snake bite [ 63 ], diarrhea [ 59 ], headache [ 64 ], and malaria [ 65 ]. In addition, it has been mentioned as an antimicrobial [ 66 ], antidiabetic [ 54 ], anti-inflammatory [ 67 ], antiprotozoan [ 68 ], antioxidant, insecticide [ 69 ], larvicide [ 70 ], and anticancer [ 71 ].…”
Section: Botanical Description and Distributionmentioning
confidence: 99%
“…A. muricata has also been used, mainly in developing tropical countries, for the treatment of arthritis [ 61 ], hypertension [ 62 ], snake bite [ 63 ], diarrhea [ 59 ], headache [ 64 ], and malaria [ 65 ]. In addition, it has been mentioned as an antimicrobial [ 66 ], antidiabetic [ 54 ], anti-inflammatory [ 67 ], antiprotozoan [ 68 ], antioxidant, insecticide [ 69 ], larvicide [ 70 ], and anticancer [ 71 ].…”
Section: Botanical Description and Distributionmentioning
confidence: 99%
“…Different classes of constituent “annonaceous” metabolites such as acetogenins are believed to play a major role in the anti-cancer properties of graviola on mammalian cells, in addition to many other constituents such as alkaloids, flavonoids, sterols and others [ 28 , 29 , 30 , 31 ]. Studies to date, all in non-skin tumor lines, suggest that the effects of graviola are selective for inhibiting the growth of cancerous cells, with minimal effects on normal cells [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…This therapeutic action of graviola might be due to its ability to selectively inhibit cancer. 5,8 Several studies have shown that low-dose radiation (LDR) has the potential to stimulate response to anticancer drugs and reduce side effects by improving therapeutic efficiency through enhancement of different phenomena such as adaptive response and cell-cell communication. 9,10 Additionally, response of the immune system 11,12 and inhibition of metastasis subsequently have been observed with LDR.…”
Section: Introductionmentioning
confidence: 99%